Frame by frame video animation (North Ryde, NSW. : Australian Film Television & Radio School, 1982)
The program talks on video animation and computer graphic
Copy available in DVD format
Executive producer, Eric Halliday
Keywords: Video art -- Technique; Animation (Cinematography)